POTENSI KETERDEDAHAN RISIKO SYARIAH SYARIKAT PENGENDALI TAKAFUL TERPILIH DI MALAYSIA(POTENTIAL OF SYARIAH RISK DISCLOSURE OF TAKAFUL COMPANIES IN MALAYSIA) - Mohamed Yusof, Mohd Faiz; Borhan, Joni Tamkin; Romli, Nurhanani (UMRAN - International Journal of Islamic and Civilizational Studies, 2016)
Nowadays, various Islamic financial products have been developed and have grown tremendously in the financial markets, including Islamic equity, Islamic banking and takaful. The Islamic finance industry has its own uniqueness compared to the conventional financial industry due to the Islamic finance industry has a need for Shariah compliance in Islamic finance industry as known as Shariah risk. Globally, Islamic capital market was faced incident of Shariah risk in the end 2007 when Sheikh Taqi Uthmani has declared that 85% of sukuk issuance in the market are non Shariah compliant in the end of 2007 and cause a decrease of sukuk issuance in the following years in 2008. There are also dispute cases in Islamic banking in Malaysia such as issue of contract Bay 'Bithaman Ajil (BBA) is not shariah compliant. The takaful industry in Malaysia is also exposed to Shariah risks due to the shariah compliance requirements in all operations and activities of the takaful operator. Therefore, this study will describe the key elements that results shariah risk in Islamic finance. The research will identified potential of shariah risk using a qualitative methodology based on research data from five informants who were experienced shariah compliance management in takaful operator. This study will analyze qualitative data using a computerized program Altas.ti 7. The study infers that there are potential of Shariah risk and incident of Shariah risk in activities and operation of selected takaful operator in Malaysia.